PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH, MURABAHAH, IJARAH TERHADAP PROFITABILITAS BANK KB BUKOPIN SYARIAH - Lestikasari, Febri; Zaman, Badrus; Linawati, Linawati (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of mudharabah, musyarakah, murabahah, ijarah financing on the profitability of Bank KB Bukopin Syariah from 2018-2022 partially and simultaneously. The population in this study is all financial report data of Bank KB Bukopin Syariah. The sample selection was carried out by purposive sampling with monthly data for the 2018-2022 period with a total sample of 60 data. The method in this study is a quantitative approach using causality techniques. This study uses data analysis methods, a classical assumption test, a multiple linear regression test and hypothesis testing. The results in this study indicate that Mudharabah Financing has an effect on profitability with sig. 0.005 < 0.05. Musyarakah has no effect on profitability indicated by sig. 0.312 > 0.05. Murabahah has an effect on profitability with sig. 0.002 <0.05. The Ijarah effect on profitability is indicated by sig. 0.012 <0.05. Simultaneously, Mudharabah, Musyarakah, Murabahah, Ijarah financing affects the profitability of Bank KB Bukopin Syariah for the 2018-2022 period.